Book Review: “Playing With My Dog Katie. An Ethnomethodological Study of Dog – Human Interaction.” by David Goode. Purdue University Press, 2007, pp. 228 - Konecki, Krzysztof Tomasz (Qualitative Sociology Review, 2007)
The book by David Goode gives us a possibility to take an extraordinary excursion to unremarkable and inscrutable world, so common for us that we do not usually notice it, although we participate in it everyday. It is a reconstructed world that shows us methods that we use in mundane life to establish an order in it and to live with others going through concrete situations. Our live consists of just these situations that we live by (as playing with a dog, talking with others, lining up the store, etc.) and not of socio – demographic data from the end of sociological questionnaires and of many other abstractions used by sociologists. What is observable and analisable not always becomes a topic of the sociological research. Ethnomethodology, a perspective used in the book, wants just to go into details and to extract them to the surface. We should not rest our analysis on the “shadows” of reality, that are cast by still available and analyzable empirical phenomena, although difficult to analyze because of sociological methods and common sense perception used by sociologists.